Designing HOTS-based Digital Media to Teach Writing: Exploring Students’ Need Analysis - Nailul Author Restu Pamungkas; Lutfina Tarita Wulandari (Universitas Sembilanbelas November Kolaka, 2020)
21st Century skills are one of the educational goals in Indonesia. One of the main goals is enable students to compete at the global level. As a consequence, HOTS-based learning is introduced through 2013 curriculum. In this case, media, materials and teachers should be able to facilitate the students getting used to implement HOTS. To fulfil these challenges, this study investigated the students’ needs which are then used as a basis in the development of digital media. This study is classified into research and development (R D). A questionnaire was employed to take the data and was distributed to 83 senior high school students. Three students voluntarily took part in the interview to confirm the results of the questionnaire. The results of this study showed that students faced difficulty in learning writing, especially in using the correct grammar and mastering English vocabulary. Consequently, they need and want the material or activity in the media that can train them to improve their understanding of grammar and vocabulary mastery. In addition, they also declared that they need to improve their HOTS, as they are still unable to use analyzing and creating skills. At the same time, the learning-need data indicated that students hoped that the developed media should provide opportunities for fellow students and teachers to mutually review writing and provide constructive comments. The material in the media is expected to provide warm-up activities in forms of videos, quizzes and problems to be discussed. All the topics provided must be relevant to their daily life.